Improvement of Stability of Rotor System by Introducing a Hydraulic Damper into an Active Journal Bearing - J. M. Krodkiewski; Y. Cen; L. Sun (International Journal of Rotating Machinery)
Modelling and analysis of a rotor--bearing system with a new type of active oil bearing is presented. The active bearing is supplied with a flexible sleeve whose deformation can be changed during operation of the rotor. The flexible sleeve is also a part of a hydraulic damper whose parameters can be controlled during operation as well.